An Overview of Mechanized Solutions for Oil Spill Treatment - Nadeem, Akbar Najar; Imtiyaz Akbar, Najar; Showkat, Ahmad Bhawani; Farooq Ahmad, Najar; Farooz Ahmad, Najar (Springer Nature, 2025)
Oil spills pose significant environmental hazards and require efficient and timely response measures for containment and cleanup. Mechanized solutions have proven to be instrumental in combating oil spills, offering effective containment, recovery, and treatment methods. This chapter provides an overview of various mechanized solutions used in the treatment of oil spills. We explore key technologies, equipment, and strategies employed in the response to oil spill incidents, emphasizing their effectiveness, limitations, and future prospects.